Recent progress in flocculation, dewatering, and drying technologies for microalgae utilization: Scalable and low-cost harvesting process development. (January 2022) - Min, Ki Ha; Kim, Dong Hyun; Ki, Mi-Ran; Pack, Seung Pil
Graphical abstract: Highlight: Efficient harvesting process is critical for practical utilization of microalgal biomass. Recent progresses in microalgal flocculation, dewatering, and drying technologies were reviewed. Each harvesting technique was discussed with consideration of energy consumption, cost, and scalability. Economically viable technologies and possible future directions were proposed for scalable and low-cost microalgal harvesting process. Abstract: Microalgal research has made significant progress in terms of the high-value-added industrial application of microalgal biomass and its derivatives. However, cost-effective techniques for producing, harvesting, and processing microalgal biomass on a large scale still need to be fully explored in order to optimize their performance and achieve commercial robustness. In particular, technologies for harvesting microalgae are critical in the practical process as they require excessive energy and equipment costs. This review focuses on microalgal flocculation, dewatering, and drying techniques and specifically covers the traditional approaches and recent technological progress in harvesting microalgal biomass. Several aspects, including the characteristics of the target microalgae and the type of final value-added products, must be considered when selecting the appropriate harvesting technique. Furthermore, considerable aspects and possible future directions in flocculation, dewatering, and drying steps are proposed to develop scalable and low-cost microalgal harvesting systems.